Pengaruh Spesies Tumbuhan Araceae terhadap Efisiensi Penularan Banana Bunchy Top Virus oleh Pentalonia nigronervosa - Rafika Oktarida; Suparman SHK; Harman Hamidson (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2022)
Araceous plants can serve as alternative host to banana aphid Pentalonia nigronervosa. Research has been conducted to study the effects of Araceous plant species on the efficiency of Banana Bunchy Top Virus (BBTV) transmission by P. nigronervosa as the main vector of the virus. The research was an experiment conducted in Experimental Garden, Department of Plant Protection, Faculty of Agriculture Sriwijaya University from November 2021 to April 2022. The experiment was conducted using 7 species of Araceous plant and one genotype of banana. The results of the research showed that, when serving as alternataive host of P. nigronervosa, all Araceous plants had no effect on the efficiency of BBTV transmission by the aphid. Viruliverous P. nigronervosa    did not lose their virus particles in their body and still had ability to transmit the virus ehen they were transferred from Araceous plant to healthy banana.In cubation period ranged from 25-37,6 days after inoculation and the symptoms appeared mostly on  young leaves.